Legal Protection for Notaries in Making a Certificate of Inheritance for the Disbursement of Savings Funds Made Based on False Documents by the Parties - Aditya Salsabila Consoleo; Benny Djaja (Journal of Law, Politic and Humanities, 2024)
The primary duty of a Notary is to create authentic deeds, and their role is particularly significant in the banking sector. For instance, in matters involving the heirs of bank customers, the preparation of an Inheritance Certificate is necessary for the disbursement of savings funds, even in cases where a false Death Certificate is presented. The purpose of this study is to investigate the legal protection available to Notaries when preparing inheritance certificates for savings disbursement based on falsified documents. A Normative Juridical Method is employed, utilizing normative legal research with a legislative and case-based approach. The findings indicate that when drafting an inheritance certificate for savings disbursement based on a fraudulent death certificate, the Notary must diligently verify the authenticity of the heirs, scrutinize the death certificate, and examine relevant documents such as identity cards, family cards, and the credentials of individuals authorized to sign the inheritance certificate. Additionally, the Notary must corroborate these details with witness statements to ensure accuracy. To address challenges in such cases, it is crucial for the Notary to exercise utmost caution. This diligence helps prevent errors whether intentional or unintentional that could invalidate the authentic deed due to inaccuracies or misrepresentation of facts. Ultimately, the Notary bears responsibility for any inaccuracies in the document they produce.